P012 ANTI-TNF DRUG ANTIBODY LEVELS CORRELATE WITH POST-SURGICAL RECURRENCE IN CROHN'S DISEASE (CD). (18th January 2018) - Pajot, Gregory; Sunjaya, Dharma; Ebner, Derek; Ho, Ivan; Eckmann, Jason; Oblizajek, Nicholas R; Papadakis, Konstantinos A
Abstract: Introduction: The prevention of the recurrence of Crohn's disease (CD) after ileo-cecal resection remains difficult. Background: Anti-tumor necrosis factor (TNF) therapy, such as infliximab or adalimumab, are both effective in preventing early disease recurrence. The Rutgeerts score was developed to define post-surgical CD recurrence and has been used to predict disease progression. The relationship between serum levels of anti-TNF agents (infliximab or adalimumab) or anti-drug antibody levels with disease activity (Rutgeerts score) after surgical resection has not been extensively investigated. Aims: The aim of our study was to correlate serum anti-TNF and anti-drug antibody levels with CD recurrence after surgical resection. Methods: We performed a retrospective analysis of patients with CD who underwent an ileocolonic resection and received anti-TNF therapy (either infliximab or adalimumab) and who completed a colonoscopy for evaluation of CD recurrence. Significant endoscopic recurrence was defined as Rutgeerts score ≥2. Results and conclusion: Fifty-six patients (24 infliximab, 32 adalimumab) were included in the study. The mean serum infliximab concentrations was 13.1 ± 26.6 μg/ml in patients with Rutgeerts score of <2 vs. 6.7 ± 12.4 μg/ml for those with a score of ≥2 (p=0.577). Similarly, the mean serum adalimumab concentration was 7.0 ± 4.6 μg/ml in patients with a Rutgeerts score of <2 vs. 3.6 ± 3.2 μg/ml for those with a Rutgeerts score of ≥2 (p=0.062). However, higher proportion of serum anti-drug antibodies was detected in patients with Rutgeerts score ≥ 2 (43% vs. 11%, p = 0.03). In patients with CD who underwent ileocolonic resection and receiving anti-TNF therapy, the presence of anti-drug antibody levels was associated with higher proportion of patient with active disease on endoscopy. Low serum anti-TNF trough levels may also reflect higher disease activity in this population but larger studies are needed to elucidate this relationship.